An investigation into some aspects of the thin layer chromatographic assay of Pregnanediol with emphasis on the suitability of this method as a clinical laboratory routine - Paton, L T (Rhodes University, Faculty of Pharmacy, Pharmacy, 1969)
Pregnanediol (5B Pregnane- 3â‹‰- 20â‹‰- dial) is the chief urinary metabolite of progesterone, and as such is important in that variations in its concentration reflect variations in progesterone secretion. Estimations of pregnanediol concentration are therefore of considerable interest to the obstetrician and gynaecologist. Pregnanediol was first identified in the urine of pregnant women in 1929 by Marrian. Nearly ten years later Venning developed a method by which the glucuronic acid ester of pregnanediol could be extracted from the urine and its concentration gravimetrically determined. Numerous variations of the Venning theme were published in the next few years, each being claimed by its authors to be an improvement on the original. Most of these involved the estimation of the conjugated form, and it was a while before the advantage of estimating the hydrolysed aglycone was realized. Hydrolysis, when it was practised, resolved itself into two methods - namely, hydrolysis by heating the urine with a mineral acid, and enzymic hydrolysis by incubation with beta-glucuronidase. Acid hydrolysis, while producing a less clean hydrolysate, is more rapid and convenient than enzyme hydrolysis, and is used in the Klapper method which is presently the most widely used method in clinical studies. Klapper employs a double chromategraphic column separation of pregnanediol followed by colorimetric evaluation. Variations of Klapper's method have also appeared and not a few investigators have published comparisons of the various methods. Klapper himself compared his method to certain other methods and concluded that his was definitely superior. Of the accuracy of the Klapper method there is no doubt. Subsequent methods have proved more sensitive, but in terms of practicability Klapper's is the method of choice. As was pointed out with some complacency, "practicability is most satisfactory, one technician readily performing some twenty determinations in one week." In contrast to the flood of criticisms, comparisons, variations, claims and counter-claims which accompanied the publication of the abovementioned methods, the thin layer chromatographic method perfected by Waldi attracted very little attention. It is very much more rapid than all other existing techniques, is very sensitive, specific and of acceptable accuracy. In an attempt to ensure its usefulness for clinical and medical research laboratories, the Waldi method has been marketed in 'kit' form. It is intended primarily as a diagnostic aid in establishing pregnancy, and as such it might have enjoyed considerable application had it not been for the advent of the immunological method of pregnancy diagnosis which is very much more rapid. Nevertheless, the Waldi method, used purely as a means of assessing the pregnanediol content of the urine is extremely useful, and it is the purpose of this investigation to establish this usefulness, especially with respect to routine clinical investigations. The validity of some diagnoses which are based on pregnanediol assay results, is also investigated. As it is impossible to explain the significance or usefulness of a pregnanediol assay without first explaining the functions of progesterone, some time and space must be expended in a brief description, firstly, of the role played by progesterone in the phenomenon of the menstrual cycle, and secondly, of its vital importance in pregnancy. It must be realized that progesterone is only one of the many hormones involved in these events, but, in order to limit the introduction of extraneous detail, no mention is made of the other hormonal participants except when necessary for the understanding of the whole. It may be mentioned here that much of the evidence that was used for the elucidation of the functions and origins of progesterone, was derived from studies of its metabolite, pregnanediol.
Keywords: Thin layer chromatography; Pregnanediol